Regional Entrepreneurial Heritage in a Socialist and Post-socialist Economy - Michael Wyrwich (European Regional Science Association (ERSA), 2010)
The main aim of this paper is to enhance our knowledge of the role of regional entrepreneurial culture that is important to foster economic growth. The paper sheds light on regional differences of self-employment and start-up activities in a socialist and post-socialist economy, which is to the authors' best knowledge a unique approach. The role of entrepreneurs in a socialist economy was marginal. Entrepreneurial activities were restricted mainly to handicrafts, retailing and gastronomy in the region of analysis of the present paper. This region is the eastern part of Germany which comprises the former socialist German Democratic Republic (GDR). It is shown by regression analysis that regions with a long industrial and entrepreneurial tradition had higher rates of self-employment in socialist times and remarkably higher start-up rates in manufacturing after the transition towards a market economy. Astonishingly those regions with a high share of traditional manufacturing industries with a long regional tradition and where entrepreneurship played an important role in pre-socialist times had higher self-employment rates in 1989. Regions with a high self-employment rate and a high share of traditional manufacturing industries in 1989 have higher start-up rates in manufacturing even more than 10 years after transition and a vast structural change in between. This result holds when controlling for industry structure and several other regional factors. Thus, even the "natural experiment" of four decades of socialism and one of the most severe industrial restructuring and decline of an economy in the 20th century could not destroy the entrepreneurial climate of regions. It seems that some regions have a certain entrepreneurial heritage, which is an important regionally embedded resource. An important implication for policy is that it seems to be long lasting task to turn entrepreneurial laggards into entrepreneurial hotspots since far reaching developments in industrial history seem to matter.
Keywords: L26; P25; R11; 330; Entrepreneurial Culture; Transition